REFLEKSI HASIL PEMBANGUNAN DAERAH PROVINSI BANTEN PERIODE 2005 - 2025 - Putra, Arta Rusidarma; Silfiana, Silfiana; Afriani, Raden Irna Irna (Jurnal Kebijakan Pembangunan Daerah, 2023)
Development evaluation is an assessment of targets and analysis of problems and success factors in a process (lesson learned) of improving regional development policies at the next stage. The aim of the research is to assess long-term development achievements with the main targets that have been determined, identify the driving and inhibiting factors that can influence the achievement of regional long-term development, and prepare recommendations for the preparation of the Regional Long-Term Program Plan for Banten Province for the period 2025-2045. The research method is literature study with secondary data in the form of research results such as articles, books, journals and several other relevant sources. Analysis techniques use gap analysis, content analysis and statistical analysis. The results of research evaluating macro indicators for 2005-2025 show progressive performance in the indicators of increasing the Human Development Index, decreasing Open Unemployment Rate, increasing per Capita Expenditure, decreasing Gini index and increasing GDP per capita. Indicators of the poor population have increased significantly and the rate of economic growth has decreased in the 2020-2021 period due to the impact of the pandemic. In 2022, the poor population will decrease and the rate of economic growth will increase in line with the post-pandemic economic recovery process. The conclusion is that it is necessary to align the vision and mission as well as the direction of policy formulation and provincial long-term development indicators with national long-term development performance indicators and indicators of sustainable development goals with the design of activity programs such as providing new jobs in the economic sector and providing various conveniences for small and medium businesses. by coordinating, collaborating and synergizing between all regional officials and various parties such as academics and practitioners as an effort to increase the achievements of macroeconomic indicators, social welfare and obtain innovation in long-term regional development plans.